2020
DOI: 10.3389/fpsyg.2020.00464
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Attachment and Internal Representations in Looked-After Children

Abstract: Background: This article explores the Story Stem Assessment Profile (SSAP), a narrative-based measure, for the assessment of internal representations in children between the ages of 4 and 11 years old. Methods: The findings draw upon two samples of children comprising of a sample of looked-after children at Five Rivers Child Care (FR) (n = 42) and a community-based population (n = 42). The FR group identified were suggested to have a higher level of need, as defined by scores obtained from the Strengths and Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 49 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…may interfere with maintaining a mentoring relationship (Grossman & Rhodes, 2002; Kupersmidt et al, 2017). Finally, some mentors also reported difficulties related to the mentee's negative attitudes or emotional state that may be linked to traumatic past experiences and attachment disruptions which, in turn, may lead to difficulties in establishing new bonds (Hillman et al, 2020; Millward et al, 2006). These psychosocial aspects should be considered when allocating and training mentors for such programmes.…”
Section: Discussionmentioning
confidence: 99%
“…may interfere with maintaining a mentoring relationship (Grossman & Rhodes, 2002; Kupersmidt et al, 2017). Finally, some mentors also reported difficulties related to the mentee's negative attitudes or emotional state that may be linked to traumatic past experiences and attachment disruptions which, in turn, may lead to difficulties in establishing new bonds (Hillman et al, 2020; Millward et al, 2006). These psychosocial aspects should be considered when allocating and training mentors for such programmes.…”
Section: Discussionmentioning
confidence: 99%
“…A vast body of research has consistently indicated that children exposed to neglect and trauma at an early age tend to form negative representations of others and of themselves [40][41][42]. These previous experiences contribute to forming their internal working models [34].…”
Section: Attachment In Adoptive Familiesmentioning
confidence: 99%
“…Within the scope of adoption, one of the most explored risk factors in research is the child s age when adopted, which is assumed to be a relevant predictor of adoption outcomes [40]. For example, early adoption is an important childhood protector from the risk of adulthood depression (which is associated with early adversity) [46].…”
Section: Attachment In Adoptive Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hillman, Cross, and Anderson [ 25 ] measured attachment representations by using a story stem approach in which attachment narratives are coded in a dimensional manner. The study compared data from a sample of children placed in foster care with a matched sample of non-maltreated children who lived with their biological parents.…”
Section: Introductionmentioning
confidence: 99%